Conjunctival Goblet Cells, the Overlooked Cells in Glaucoma Treatment. Issue 4 (April 2019) - Tiedemann, Daniel; Mouhammad, Zaynab A.; Utheim, Tor P.; Dartt, Darlene A.; Heegaard, Steffen; Petrovski, Goran; Kolko, Miriam
Abstract : Glaucoma is the leading cause of irreversible blindness worldwide. Although no definitive cure exists, lowering of the intraocular pressure decreases the rate of progression in the majority of patients with glaucoma. Antiglaucomatous treatment modalities consist predominantly of chronic use of eye drops. It has become increasingly evident that long-term exposure to eye drops has a significant impact on the ocular surface, and thereby on patient compliance and quality of life. Maintenance of the ocular surface is highly dependent on a stable tear film. Conjunctival goblet cells (GCs) of the ocular surface play an important role in providing the innermost mucin layer of the tear film and are essential for maintaining the ocular surface homeostasis. Recent studies have reported severe side effects of antiglaucomatous drops on GCs. In particular, a preservative containing antiglaucomatous drops have been shown to affect the viability and functions of the GCs. Furthermore, GC density has been suggested as a potential predictor of surgical outcome after filtration surgery. The present review provides an overview of the current literature on the impact of antiglaucomatous eye drops on GCs as well as the impact on the ocular surface. Moreover, the existing evidence of a possible association between GC density and glaucoma filtration surgery outcome is summarized. We conclude that prostaglandin analogs spare the conjunctival GCs more compared with other antiglaucomatous drops and that GCs may be a good predictor of surgical outcome after filtration surgery. Overall, given the multiple functions of GCs in the ocular surface homeostasis, dedicated strategies should be adopted to preserve this cell population during the course of glaucoma.